2021
DOI: 10.3389/fmicb.2021.627595
|View full text |Cite
|
Sign up to set email alerts
|

Novel Microbial Groups Drive Productivity in an Archean Iron Formation

Abstract: Deep subsurface environments are decoupled from Earth’s surface processes yet diverse, active, and abundant microbial communities thrive in these isolated environments. Microbes inhabiting the deep biosphere face unique challenges such as electron donor/acceptor limitations, pore space/fracture network limitations, and isolation from other microbes within the formation. Of the few systems that have been characterized, it is apparent that nutrient limitations likely facilitate diverse microbe-microbe interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 138 publications
(210 reference statements)
0
8
0
Order By: Relevance
“…However, there were some differences in the respective compositions of some long-chain fatty acids, such as C18:1 ω5c, C19:0 iso, and C20:1 ω7c. The respiratory quinones of strains NC18 T and NC20 were Q-10, typical for the genus Martelella [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, there were some differences in the respective compositions of some long-chain fatty acids, such as C18:1 ω5c, C19:0 iso, and C20:1 ω7c. The respiratory quinones of strains NC18 T and NC20 were Q-10, typical for the genus Martelella [ 1 , 2 , 3 , 4 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data for strain 1 from this study. Data for strain 3 from Rivas et al [ 1 ], strains 4 and 8 from Chung et al [ 4 ], strain 5 from Bibi et al [ 2 ], strains 6 and 9 from Zhang et al [ 3 ], strain 7 from Kim et al [ 6 ], and strain 10 from Lee [ 5 ]. +, positive; -, negative; w, weak; NR, not reported.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Microbially-driven anaerobic oxidation of ammonium (e.g., Van De Graaf et al, 1995;Byrne et al, 2008) is a more efficient mechanism to convert ammonium to N2. Microbial recycling of nitrogen has been suggested to occur in subsurface fracture fluids in the Kaapvaal Craton (Silver et al, 2012;Lau et al 2016) and elsewhere in the Canadian Shield (Sheik et al, 2021), but cannot be explored further for the KC samples due to the lack of biogeochemical data and isotopic compositions of other nitrogen species (ammonium, nitrite or nitrate, if there is any) in these fracture fluids. It is worth highlighting though that recent studies using cell counts and culture-based methods have identified low abundance of H2-utilizing, alkane-oxidizing sulfate-reducing bacteria in the KC fracture fluids (Lollar et al, 2019;Wilpiszeski et al, 2020).…”
Section: Microbial Nitrogen Recycling?mentioning
confidence: 99%